CONTRIBUTION OF THE GIFT THEORY TO TERRITORIAL STUDIES (Desenvolvimento em Questão, 2020)
Marcel Mauss is the great creator of the theory of gift, which allows, among other possibilities, to analyze how exchange and symbolism enable socialization and communication between actors. In this article, we seek to identify its contribution, through the gift theory, to the development of new territorial studies. Our objective here, therefore, is to check, in the light of this theory, how exchange relations and the presence of symbolism occur in open markets on the Brazil-Bolivia border, through qualitative work and under an ethnographic approach. At the same time, we discussed the contribution of Economic Sociology and New Economic Sociology to urban, sustainable and regional studies due to the contribution of the francophone current of ‘gift’. From a theoretical-empirical construction applied to a case analysis, it is possible to state that the gift theory allows the recognition of several social phenomena present in the territory, with an emphasis on the actor, and how important this is for the development of the region. It also made it possible to perceive the importance of studying the markets from an economic, sociological, historical perspective, that is, as social constructions, since, in the case of fairs, some exchanged symbols were identified, which made it possible to create a look beyond utilitarianism and understand how the dynamics of territory development occurs and the existence and maintenance of fairs.
Keywords: Gift Theory, Development, Territorial Studies. New Economic Sociology.